2018
DOI: 10.1007/s00210-018-1508-2
|View full text |Cite
|
Sign up to set email alerts
|

Decreased contraction induced by endothelium-derived contracting factor in prolonged treatment of rat renal artery with endoplasmic reticulum stress inducer

Abstract: Recent evidence suggests that endoplasmic reticulum (ER) stress is involved in the regulation of various physiological functions, including those of the vascular system. However, the relationship between ER stress and vascular function is poorly understood. The endothelial cells control the vascular tone by releasing endothelium-derived relaxing factors and contracting factors (EDCFs). We hypothesized that tunicamycin, an inducer of ER stress, modifies endothelium-dependent contraction and prostaglandins (PGs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…The present study used organ culture techniques to investigate the direct associations among equol, insulin, and vascular function without the influence of complicated factors from other organs. [26][27][28][29][30][31] After prolonged treatment with equol and high insulin, each carotid arterial ring was mounted in an organ bath system where equol and insulin were completely removed. Thus, alterations of vascular function are resulted from prolonged but not acute effects.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The present study used organ culture techniques to investigate the direct associations among equol, insulin, and vascular function without the influence of complicated factors from other organs. [26][27][28][29][30][31] After prolonged treatment with equol and high insulin, each carotid arterial ring was mounted in an organ bath system where equol and insulin were completely removed. Thus, alterations of vascular function are resulted from prolonged but not acute effects.…”
Section: Resultsmentioning
confidence: 99%
“…Organ Culture Procedure and Vascular Function Study The organ culture procedures and measurements of vascular functions were as performed according to our previous studies. [26][27][28]30,32) Briefly, common carotid artery was isolated from a rat anesthetized with isoflurane and euthanized by exsanguination. The carotid artery was cleaned of adhering fat and connective tissue, cut into rings under sterile conditions, and placed in the medium consisted of low-glucose (5.5 mmol/L) Dulbecco's modified Eagle's medium (DMEM) (Gibco BRL, Grand Island, NY, U.S.A.) supplemented with 1% fetal bovine serum (Biological Industries, Kibbutz Beit Haemek, Israel) and 1% penicillin/streptomycin (Gibco BRL).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several reports suggest that ER stress can be associated with hypertension and vascular remodelling [14]. It has been shown that the induction of ER stress in renal arteries reduces endothelium-derived relaxing factors and contracting factor (EDCF)-mediated contractions [15]. In the case of hypovolemia, blood flow is predominantly redirected to vital organs, such as liver, through a process known as 'centralized' circulation, which is believed to be achieved exclusively via peripheral vasoconstriction.…”
Section: Of 14mentioning
confidence: 99%